The Implementation of Inclusive Education in Indonesia: Challenges and Achievements - Zola Permata Sari; Riska Sarofah; Yusuf Fadli (Universitas Teuku Umar, 2022)
This study aims to show the factors in the successful implementation of inclusive education in Indonesia. And what causes obstacles to the implementation of inclusive education. This study uses a literature review through reading media from several national and international journals in the last 10 years that meet the criteria. The results show that the implementation of inclusive education in Indonesia has been quite successful in several big cities. This success is due to several supporting factors such as the existence of special educators, class management, and curriculum. However, there are still many small cities in Indonesia that are still not successful due to the unavailability of adequate facilities and lack of information about the inclusive education system. The government should not only pay attention to big cities but also pay attention to the problem of implementing inclusive education in small cities and make it easier to see data on the number of students with disabilities each year.